Optimizing the Physical Training of Military Trainees. Issue 4 (August 2015) - Orr, Robin M.; Pope, Rodney
Abstract : ABSTRACT: INITIAL MILITARY TRAINING IS DESIGNED TO PREPARE NEW TRAINEES FOR THE REQUIREMENTS OF MILITARY SERVICE. PROVIDING A PHYSICAL TRAINING PROGRAM TO OPTIMIZE INITIAL TRAINING SUCCESS WHILE MINIMIZING THE POTENTIAL FOR INJURY, ESPECIALLY OVERUSE INJURY, IS VITAL. SEVERAL KEY FACTORS, INCLUDING INITIAL TRAINEE FITNESS, OTHER TRAINING REQUIREMENTS, AND PROGRAM-INDUCED CUMULATIVE OVERLOAD, NEED TO BE CONSIDERED WHEN DEVELOPING AND IMPLEMENTING A PHYSICAL TRAINING PROGRAM FOR A MILITARY TRAINEE. THE USE OF AN UNDULATING MODEL, INCORPORATING ELEMENTS OF METABOLIC AND NEUROMUSCULAR CONDITIONING, AS WELL AS LOAD CARRIAGE CONDITIONING SHOULD FORM THE FRAMEWORK OF A MILITARY TRAINEE'S PHYSICAL TRAINING PLAN.